Gene therapy for Glut1‐deficient mouse using an adeno‐associated virus vector with the human intrinsic GLUT1 promoter. (6th April 2018) - Nakamura, Sachie; Muramatsu, Shin‐ichi; Takino, Naomi; Ito, Mika; Jimbo, Eriko F.; Shimazaki, Kuniko; Onaka, Tatsushi; Ohtsuki, Sumio; Terasaki, Tetsuya; Yamagata, Takanori; Osaka, Hitoshi
Abstract: Background: We generated an adeno‐associated virus (AAV) vector in which the human SLC2A1 gene, encoding glucose transporter type 1 (GLUT1), was expressed under the human endogenous GLUT1 promoter (AAV‐GLUT1). We examined whether AAV‐GLUT1 administration could lead to functional improvement in GLUT1 ‐deficient mice. Methods: We extrapolated human endogenous GLUT1 promoter sequences from rat minimal Glut1 promoter sequences. We generated a tyrosine‐mutant AAV9/3 vector in which human SLC2A1‐myc‐DDK was expressed under the human GLUT1 promoter (AAV‐GLUT1). AAV‐GLUT1 was administered to GLUT1 ‐deficient mice (GLUT1 +/– mice) via intracerebroventricular injection (1.85 × 10 10 vg/mouse or 6.5 × 10 10 vg/mouse). We analyzed exogenous GLUT1 mRNA and protein expression in the brain and other major organs. We also examined improvements of cerebral microvasculature, motor function using rota‐rod and footprint tests, as well as blood and cerebrospinal fluid (CSF) glucose levels. Additionally, we confirmed exogenous GLUT1 protein distribution in the brain and other organs after intracardiac injection (7.8 × 10 11 vg/mouse). Results: Exogenous GLUT1 protein was strongly expressed in the cerebral cortex, hippocampus and thalamus. It was mainly expressed in endothelial cells, and partially expressed in neural cells and oligodendrocytes. Motor function and CSF glucose levels were significantly improved following intracerebroventricular injection. Exogenous GLUT1 expression was not detected in other organs after intracerebroventricular injection of AAV‐GLUT1, whereas it was detected in the liver and muscle tissue after intracardiac injection. Conclusions: Exogenous GLUT1 expression after AAV‐GLUT1 injection approximated that of physiological human GLUT1 expression. Local central nervous system administration of AAV‐GLUT1 improved CSF glucose levels and motor function of GLUT1 ‐deficient mice and minimized off‐target effects.